Pendampingan Melalui Agribisnis Syariah: Membangun Ketahanan Pangan dan Ekonomi Pedesaan di Desa Morbatoh Banyuates - Muhammad Mamun; Ahmad Walid (Journal of Research and Community Service, 2024)
This activity aims to explore the potential of sharia agribusiness in improving food security and rural economy in Morbatoh Banyuates village, Indonesia. With a participatory approach, this activity involves local communities, including farmers and agribusiness actors, to identify local resources, community needs, and the impact of the training provided. The research method used is qualitative descriptive, which includes initial surveys, in-depth interviews, and training on sustainable agricultural practices. The results of mentoring and training show that the implementation of sharia agribusiness has succeeded in increasing people's knowledge and skills in managing agricultural businesses, which has a positive impact on increasing food production and income. The average rice production increased from 3 tons to 4.5 tons per hectare, and farmers' income increased from Rp 2,000,000 to Rp 3,500,000 per month. The implications of this activity show that sharia agribusiness can be an effective solution to empower rural communities, increase food security, and create sustainable economic welfare. Therefore, it is important to continue the sharia agribusiness development program by strengthening training and access to appropriate capital and technology.